Inovasi Model Kelembagaan Kawasan Industri Prakarsa Pemerintah - Winardi Winardi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
Industrial estates have experienced rapid development in the last 10 years, where there are around 132 industrial estates that have been operating throughout Indonesia. However, the industrial institutional model has not changed much since the first industrial estate was established in the 1970s, which is limited to the management carried out by business entities either by BUMN/BUMD, Cooperatives and Limited Company. In this regard, this study was conducted in order to innovate the development and management of industrial estates, especially those initiated by the government through the Public Private Partnership scheme. The method used is a qualitative method with a desk study approach and Focus Group Discussion. The results of this study recommend the Government to establish a technical agency unit in the form of the National Industrial Estate Development Agency in the form of PK BLU to carry out the main tasks and functions in building and managing competitive industrial estates so that it is expected to accelerate the spread of industrial estate development throughout Indonesia.